Contestation of the Determination of ‘Idul Adha and its Implementation According to Muhammadiyah and Nahdatul ‘Ulama - Rahmi, Nailur; Rizki, Muh; Fajriati, Nurul Azniah; Nurlaila, Nurlaila; Efendi, Faisal; Linda Sari Bulan Siregar (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
Muhammadiyah and Nahdlatul Ulama differ in determining the date of Idul Adha, primarily due to the distinct methodologies they employ and the underlying factors contributing to the resulting controversy. The to understand and describe the contestation, methods of determining Eid al-Adha, as well as to analyze the causes of these differences. Uses data from various articles and information related to the determination of Eid al-Adha within the scope of Muhammadiyah and Nahdlatul Ulama. The collected data were analyzed and subsequently compared to generate well-founded conclusions. The research results, Muhammadiyah uses a calculation method with the criterion of wujudul hilal, while the Nahdlatul Ulama uses the Imkanur Rukyat method with the MABIMS criterion, which requires the hilal to be 3 degrees above the horizon. Prioritizes the rukyat method. The cause of this difference lies in the varying interpretations of the hadiths used as the basis for determining the beginning of the Islamic lunar month, which leads to differences in the criteria for the height of the hilal. Muhammadiyah understands the Lafadz “faqduruu lah” in the Hadith to be an order from Allah to calculate the beginning of the month by means of hisab.This is close to results that can provide certainty, because it is calculated by sophisticated methods and technology. Nahdatul ‘Ulama, the wording of the Hadith demands the determination of the beginning of the month in accordance with the rules that Allah has set, by observing the hilal, not by calculations that are purely human thinking. If the hilal is not visible, then the age of the month is 30 days. These methodological differences lead to variations in the observance of Idul Adha, disrupt uniformity in worship practices and the national calendar, and therefore require the Muslim community to exercise caution and wisdom in navigating and managing such differences.